2000
DOI: 10.1054/bjoc.1999.1010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of vascular maturation in breast cancer blood vessels to vascular density and metastasis, assessed by expression of a novel basement membrane component, LH39

Abstract: Angiogenesis, the formation of new vessels, has been demonstrated to be an indicator of prognosis in breast cancer patients. The extent of differentiation of the tumour vessels may affect access of peripheral white cells and egress or invasion of tumour cells. This has not been assessed in relation to tumour microvessel density or other variables and may be a marker of vascular remodelling. LH39 is a monoclonal antibody recognizing an epitope located at the lamina lucida of mature small veins and capillaries b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…In all the cases classified as angiogenic we have confirmed that most of the vessels have an immature phenotype, with deficient LH39 expression, as observed previously in oral carcinoma (Almeida et al, 1992b), breast carcinoma (Kakolyris et al, 2000), and another series of n-SCLC (Kakolyris et al, 1999). It should be noted that a variable number of mature vessels is still present.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In all the cases classified as angiogenic we have confirmed that most of the vessels have an immature phenotype, with deficient LH39 expression, as observed previously in oral carcinoma (Almeida et al, 1992b), breast carcinoma (Kakolyris et al, 2000), and another series of n-SCLC (Kakolyris et al, 1999). It should be noted that a variable number of mature vessels is still present.…”
Section: Discussionsupporting
confidence: 88%
“…These data suggest that the detection of LH39 allows the discrimination between mature and recently formed vessels. Most of the intra-tumoural vessels should therefore be negative for LH39 and three studies, on oral carcinomas (Almeida et al, 1992b), on breast carcinomas (Kakolyris et al, 2000) and on lung cancer (Kakolyris et al, 1999) have confirmed this hypothesis. Even in the case of breast cancer, the number of LH39-negative intra-tumoural vessels is significantly higher than in normal breast tissue (where some LH39 negative, immature vessels are present because of the physiological remodelling of the tissue).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, tumour vasculature is, among others, marked by a high rate of endothelial cell proliferation, the absence of pericytes, abnormalities in the basement membrane and often an increased vascular permeability. Structurally, disorganised, tortuous, thinwalled vessels are seen that lack smooth muscle and pericyte coats and innervation (Figure 1) (Kakolyris et al, 2000;Konerding et al, 2001). Blood flow frequently is sluggish and at times might be stationary or even in a reversed direction (Tozer et al, 1990).…”
Section: Vdas and Their Targetmentioning
confidence: 99%
“…These differences could be exploited by selective drugs or agents, now called vascular disrupting agent (VDAs) or vascular targeting agents (VTA) (94). Several reports have shown that biological differences between normal and tumor vascular endothelium (Table II) can provide a scientific rationale for vascular targeting and therapeutic benefits (37,(94)(95)(96)(97)(98)(99)(100)(101). Multiple tumor endothelial markers that are not expressed on normal vascular endothelium are now being characterized and used for specific targeted purposes (97).…”
Section: Vascular Disrupting Strategiesmentioning
confidence: 99%